Hypertrophic Cardiomyopathy Mimicking Acute Anterior Myocardial Infarction Associated with Sudden Cardiac Death. (16th August 2012) - Daralammouri, Y.; El Garhy, M.; Same, K.; Lauer, B.
Abstract : Hypertrophic cardiomyopathy is the most common genetic disease of the heart. We report a rare case of hypertrophic obstructive cardiomyopathy mimicking an acute anterior myocardial infarction associated with sudden cardiac death. The patient presented with acute ST elevation myocardial infarction and significant elevation of cardiac enzymes. Cardiac catheterization showed some atherosclerotic coronary artery disease, without significant stenosis. Echocardiography showed left ventricular hypertrophy with a left ventricular outflow tract obstruction; the pressure gradient at rest was 20 mmHg and became severe with the Valsalva maneuver (100 mmHg). There was no family history of sudden cardiac death. Six days later, the patient suffered a syncope on his way to magnetic resonance imaging. He was successfully resuscitated by ventricular fibrillation.